Creation of Specialized Manipulators for Low Temperature Research - Zharkov, I.P.; Safronov, V.V.; Khodunov, V.O.; Konoval, V.M.; Maslov, V.O.; Selivanov, O.V.; Solonetsky, A.G.; Strelchuk, V.V.; Nikolenko, А.S.; Tsykaniuk, B.I.; Naseka, V.M. (Science and Innovation, 2024)
Introduction. Magneto- and electro-optical research of materials at cryogenic temperature requires expensive specialized cryostats. In the case of research in magnetic fields up to 1 T special manipulator holders can be used. Problem Statement. Development of special manipulators for cryostats to enable the magneto-optical research of materials under the action of external magnetic and electric fields is a relevant problem for low temperature studies. Purpose. The purpose is to create specialized manipulators for electro- and magneto-optical measurements at cryogenic temperature. Results. Special sample holding manipulators have been developed. They enable to conduct low-temperature measurements at cryogenic temperature in a constant magnetic field up to 1 T in the continuous-flow cryostat. The design enables varying the field by changing the gap between the magnets. The magnetic field line direction is changeable with respect to the direction of light propagation. The developed manipulator allows the researchers to study the optical properties of materials depending on applied electric field, at low temperature and to supply electric field to the samples, as well as to record electrical signals from the sample. The use of sample holding manipulators enables measuring several samples in one cycle of cryostat fill. Conclusion. Special manipulators have been designed to study the magneto- and electro-optical properties of materials at low temperature. With the help of developed manipulators, it is possible to measure the influence of magnetic and electric field on the optical properties of the materials studied. The research has been carried out within the framework of the Program of Research Instrument-Making of the NАS of Ukraine, grant No. P- 2/16-40.